Henry has arisen: Gender and hierarchy in Vanuatu's Anglican Church. (21st April 2016) - Lind, Craig
Abstract : Although Christianity and kastom can be opposed in many important respects, ni‐Vanuatu2 are far from limited by the different opportunities that they each offer. Here, I draw on gender as an ethnographically derived form of description to stress that the relations composing encounters of Christianity and kastom, church leader and chief, allow ni‐Vanuatu to imagine and create possibilities for engaging these alternatives in order to share, exchange or take on their specific capacities. I consider the example of an event in which a Church leader offered to extend an emplaced island identity, through the Anglican Church, in exchange for a kastom chief's assistance to scale‐up the appearance of his clan support during his ordination ceremony. In this case gendered difference, and not opposition or conflict, characterises kastom and Christianity's relationship.